2022
DOI: 10.1177/00031348221078984
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Outcomes for Trauma Patients in Prison and the General Population

Abstract: Background Prisoners are a vulnerable population, and there are few contemporary studies that consider trauma patient outcomes within the prisoner population. Therefore, we sought to provide a descriptive analysis of prisoners involved in trauma and evaluate whether a healthcare disparity exists. We hypothesized that prisoners and non-prisoners have a similar risk of mortality and in-hospital complications after trauma. Methods The Trauma Quality Improvement Program (2015-2016) was queried for trauma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The prison population had similar mortality and morbidity but a slightly shorter length of stay. 4 Before the current report, little had been published about nontrauma surgical care of incarcerated individuals.…”
Section: Invited Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…The prison population had similar mortality and morbidity but a slightly shorter length of stay. 4 Before the current report, little had been published about nontrauma surgical care of incarcerated individuals.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Numerous medical and cultural challenges arise in caring for incarcerated individuals, and academic medical centers have provided much of the medical care for incarcerated persons . Some studies previously attempted to characterize medical and trauma care within penitentiaries. Those studies showed that more than 40% have chronic medical conditions along with higher frequencies of hypertension, obesity, and smoking .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the literature surrounding the correctional health care system is written from the public health perspective and discusses treatment of communicable diseases (eg, HIV or hepatitis C) and access to mental health services, with a notable lack of data on surgical treatments and outcomes . To our knowledge, the largest studies of patients who are incarcerated and treated by a surgical team have focused on trauma and acute care surgery, with studies conducted by the Eastern Association for the Surgery of Trauma and using large trauma databases . While these studies provided important insight, a considerable proportion of surgical patients, such as those who present for less urgent or elective procedures, remains excluded.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 To our knowledge, the largest studies of patients who are incarcerated and treated by a surgical team have focused on trauma and acute care surgery, with studies conducted by the Eastern Association for the Surgery of Trauma and using large trauma databases. [7][8][9] While these studies provided important insight, a considerable proportion of surgical patients, such as those who present for less urgent or elective procedures, remains excluded. This study sought to evaluate quality outcomes from a broader range of surgical patients and subspecialties by using data from one of the largest correctional hospitals in the US, while also comparing these metrics to institutional and national benchmarks.…”
mentioning
confidence: 99%